2019
DOI: 10.29252/jhc.21.3.242
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Sex Schemas and Sexual Satisfaction of Couples: The Mediating Role of Communication Patterns

Abstract: Background & Aims: Couples communication patterns have some roles in all areas of their common life. Also, the individual satisfaction of each spouse, especially in performance and sex, can be influenced by their communication skills and patterns. The present study was conducted to investigate the relationship between sexual schemas and sexual satisfaction of couples and mediating role of communication patterns. Methods: The present study was a descriptive-correlational research. The research population consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…They revealed that women who had a shy-cautious sexual schema had a negative body image and as a result, poor sexual function [ 50 ]. Recognizing the factors affecting women’s sexual function such as sexual schemas, and paying attention to these factors by health care professionals can improve communication patterns and provide sexual health services to them [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…They revealed that women who had a shy-cautious sexual schema had a negative body image and as a result, poor sexual function [ 50 ]. Recognizing the factors affecting women’s sexual function such as sexual schemas, and paying attention to these factors by health care professionals can improve communication patterns and provide sexual health services to them [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The validity and reliability of this questionnaire were measured in the research by Bahrami et al [13]. Cronbach's alpha coefficient was more than 0.87 [1].…”
Section: Methodsmentioning
confidence: 99%
“…The maximum score of the questionnaire is 270. In the research, the content and form of the questionnaire have been evaluated by the hypothetical content and form [1]. The calculated Cronbach's alpha coefficient in the quasi-research questionnaire was estimated to be above 0.87 [1].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation